The Continental Model : Selected French Critical Essays of the Seventeenth Century in English Translation - Elledge, Scott (Book collections on Project MUSE., 1960)
The pervasive influence of seventeenth-century French criticism upon eighteenth-century English criticism makes it important for students of English and comparative literature to be familiar with the most important of the French works. Professors Elledge.